2000
DOI: 10.1007/s000110050636
|View full text |Cite
|
Sign up to set email alerts
|

Specific binding of IL-8 to rabbit α -macroglobulin modulates IL-8 function in the lung

Abstract: The data suggest that alphaM may facilitate IL-8 clearance from the lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…In addition, this is the first study to define the activity of IL-8 in ␣ 2 -M/IL-8 complexes purified from pulmonary edema fluid. Thus our observations are more closely related to in vivo conditions than our prior studies of the in vitro activity of IL-8 (13)(14)(15).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In addition, this is the first study to define the activity of IL-8 in ␣ 2 -M/IL-8 complexes purified from pulmonary edema fluid. Thus our observations are more closely related to in vivo conditions than our prior studies of the in vitro activity of IL-8 (13)(14)(15).…”
Section: Discussionsupporting
confidence: 62%
“…On the other hand, our previous findings suggested that ␣ 2 -M could be an important mediator of IL-8 clearance (13,15). Those studies indicated that alveolar macrophages have receptors for ␣ 2 -M but not for IL-8.…”
Section: Discussionmentioning
confidence: 92%
“…CXCR1 is specific for IL-8 (40,41), and within this study we have found that IL-8 interacts with glycosylated AAT, but rather than facilitating IL-8 activity, physiological concentrations of AAT inhibit CXCR1 engagement of up to 20 ng of IL-8, thereby preventing downstream signaling events including Akt phosphorylation, calcium flux, and chemoattractant-induced cytoskeletal rearrangements. This antiinflammatory effect is not exclusive to AAT, as it has also been reported that the plasma glycoprotease inhibitor α-2 macroglobulin creates a complex with IL-8, resulting in reduced neutrophil infiltration into the lungs compared with IL-8 controls (42). AAT and α-2 macroglobulin are acute-phase reactants, and as both proteins show a rise in mean value after infection, it is tempting to speculate that the increased levels of both serum proteins function to dampen down the inflammatory response after infection by binding and inactivating IL-8 activity.…”
Section: Discussionmentioning
confidence: 70%
“…There are many reports describing the effects of clusterin, haptoglobin and α 2 M on the immune system (59,(176)(177)(178)(179)(180). Some of these, such as the ability of α 2 M to enhance antigen presentation (91) and haptoglobin-facilitated clearance of hemoglobin (180), clearly fall outside of the scope of this review and as such, will not be discussed here.…”
Section: Anti-inflammatory Effects Of Ecsmentioning
confidence: 99%